Risk factors for binge eating disorder: a community-based, case-control study. - Fairburn, C; Doll, H; Welch, S; Hay, P; Davies, B; O'Connor, M (American Medical Association, 1998)
BACKGROUND: Many risk factors have been implicated for eating disorders, although little is known about those for binge eating disorder. METHODS: A community-based, case-control design was used to compare 52 women with binge eating disorder, 104 without an eating disorder, 102 with other psychiatric disorders, and 102 with bulimia nervosa. RESULTS: The main risk factors identified from the comparison of subjects with binge eating disorder with healthy control subjects were certain adverse childhood experiences, parental depression, vulnerability to obesity, and repeated exposure to negative comments about shape, weight, and eating. Compared with the subjects with other psychiatric disorders, those with binge eating disorder reported more childhood obesity and more exposure to negative comments about shape, weight, and eating. Certain childhood traits and pronounced vulnerability to obesity distinguished the subjects with bulimia nervosa from those with binge eating disorder. CONCLUSIONS: Binge eating disorder appears to be associated with exposure to risk factors for psychiatric disorder and for obesity. When compared with the wide range of risk factors for bulimia nervosa, the risk factors for binge eating disorder are weaker and more circumscribed. Pre-morbid perfectionism, negative self-evaluation, and vulnerability to obesity appear especially to characterize those in whom bulimia nervosa subsequently develops.